Kinerja Dinas Koperasi UKM Dan Tenaga Kerja Dalam Pembinaan Usaha Kecil Menengah (UKM) Di Kota Banjarbaru - Aulia Aulia (Jurnal Administrasi Publik dan Pembanguan, 2019)
The performance of the SME Department of Cooperatives and labor in the construction of small to medium enterprises (SMEs)are categorized as either. It is seen from the indicators of productivity where with the holding of the training Department of the perpetrators of the SMES are satisfied and very beneficial to them, but from the side to the principals logging productivity SMES that have not been built can be assessed yet satisfying because of the lack of the information obtained and the lack of socialization which is given by the employees, the quality of service been good as it seemed a fairly adequate facilities and the friendly attitude of the employees , maximum, already seenresponsiveness complaint SMES that directly addressed quickly by the Agency,corporate responsibility has not been entirely good looks ketidakterbukaan information on training activities, as well as exhibitions and accountability is already well out of sight of no constraint in accountability to the Central Government or local governments.